Ecological Architectural Concepts of Museum Buildings in the Humid Tropics (Case Study: Museum Gunungapi Merapi) - Widya Lintang Iriani; Heru Subiyantoro (Arsitektura : Jurnal Ilmiah Arsitektur dan Lingkungan Binaan, 2023)
Ecological architecture is the harmony between structural function and environmental function through the efficient usage of natural potential and adherence to eco-friendly principles. The purpose of this study is to see how ecological architecture is applied in the design of museum buildings. The object of this research is the Museum Gunungapi Merapi. The building is located in Yogyakarta, near Mount Merapi, a humid tropical area. This qualitative descriptive research illustrates the factual conditions of the museum, which later on will be associated with theories found in literatures. A building will be regarded as ecological if its design has met ecological architectural principles in the sense of having incorporated environmental consideration in its physical structure, harmonized its system with nature, used sustainable natural resources and energy efficiency, and applied spatial planning according to ecological values. The results have led to a conclusion that the museum has been built by considering the ecological architectural aspects of its structural arrangement, landscape utilization, and material usage.